Estudo das atividades antinociceptiva, anti-inflamatória e antioxidante da Sideroxylon obtusifolium (Sapotaceae) - Araújo Neto, Vitor (2009)
Sideroxylon obtusifolium belongs to the family Sapotaceae. This study aimed to contribute to the scientific knowledge of the antinociceptive, anti-inflammatory and antioxidant properties of the steam bark of Sideroxylon obtusifolium (Roem. & Schult.) T.D. Penn, popularly known as quixabeira and used to treat pain and inflammation. The ethanol crude extract of the dried and triturated stem bark (EE, 459,60 g) was submitted to liquidliquid extraction (400 g) with hexane, chloroform and ethyl acetate to give fractions hexane (11,90 g), chloroform (6,08 g), ethyl acetate (43,72 g) and hydromethanol (181,35 g). The EE and its fractions were submitted to phytochemical analysis, which detected groups of secondary metabolites such as phenols, flavanoids, xanthones, steroids, triterpens, saponins, tannins and cathechins. The effects of the extract and its fractions in nociception (using the models of abdominal writhing induced by acetic acid, hot plate and formalin in mice), inflammation (using the models of paw edema and peritonitis induced by carrageenan in mice) and antioxidant (using the scavenging of DPPH method) were evaluated. In the model of abdominal writhing induced by acetic acid, the oral treatment with of EE at 400 mg/kg had similar inhibition to that of AAS. The model of hot plate showed that the EE did not cause an increase in the latency time by the thermal stimulus at 55 ± 0.5°C, suggesting does not have central antinociceptive action. The EE only inhibited the second phase in the formalin test, which suggested that had inflammatory antinociception, which showed possibly acts by inhibiting the enzyme ciclo-oxygenase (COX). When evaluating the anti-inflammatory action by the carrageenan-induced paw edema model, the oral feeding of the EE was effective in reducing the edema-forming response between second and fourth hour after injecting carrageenan. Peritonitis model showed that the oral administration of EE was effective in reducing the leukocyte migration after 4 h of the i.p. injection of carrageenan, which was similar to dexamethasone. The DPPH assay showed the EE and its fractions ethyl acetate and hydromethanol present a antioxidant activity in vitro, which can be related to the presence of polyphenols. Therefore, the extract of S. obtusifolium has relevant phytochemical, which can be influencing the anti-inflammatory, analgesic, and antioxidant activities, suggesting it can be submitted to new pharmacological studies and clinical trial.